2021
DOI: 10.1055/s-0041-1723992
|View full text |Cite
|
Sign up to set email alerts
|

Complicated Acute Appendicitis during COVID-19 Pandemic: The Hidden Epidemic in Children

Abstract: Introduction Since home confinement for novel coronavirus disease 2019 (COVID-19) pandemic began, pediatric visits to the emergency department (ED) have decreased, including consultation for abdominal pain. Our aim is to investigate the incidence of complicated acute appendicitis (AA; peritonitis or appendicular mass) during confinement for COVID-19 pandemic and to compare it with the previous 5 years. Materials and Methods A retrospective study was performed in children with AA who underwent surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Concerns about delays in diagnosis were realized in reports of severe illness and deaths due to diabetic ketoacidosis, pyloric stenosis, sepsis and cancer in children presenting to the hospital after delays attributed to fear of COVID-19 and reduced access to care 55 , 56 . Delays in presentation were suspected to contribute to an increase the rate of complicated appendicitis in more than one series 56 , 57 , 58 , 59 . A study of a large sample of emergency departments in the US revealed a drop in pediatric visits by up to 72% compared to the same week one year prior 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about delays in diagnosis were realized in reports of severe illness and deaths due to diabetic ketoacidosis, pyloric stenosis, sepsis and cancer in children presenting to the hospital after delays attributed to fear of COVID-19 and reduced access to care 55 , 56 . Delays in presentation were suspected to contribute to an increase the rate of complicated appendicitis in more than one series 56 , 57 , 58 , 59 . A study of a large sample of emergency departments in the US revealed a drop in pediatric visits by up to 72% compared to the same week one year prior 60 .…”
Section: Discussionmentioning
confidence: 99%
“…46 As a result, many centers reported during the first wave of the COVID-19 pandemic a statistical significant increase in perforated AA in pediatric patients relative to previous years, ranging between 32 and 60.5%. 32,45,52,54,60,61 Interestingly, there have been no obvious changes in patient demographics during this time to explain this increase. However, some children with AA were seen more promptly in the ED and appendectomies were frequently performed sooner due to the reduction in elective surgeries.…”
Section: Duration Of Appendicitis Symptoms Before Presentation During the Global Covid-19 Pandemicmentioning
confidence: 98%
“…However, in our view there is nothing specifically pediatric in his observations. Several recent papers discuss delays of diagnosis and treatment of non-COVID-19 diseases during the pandemic, including head and neck cancer, 2 appendicitis, 3 , 4 heart failure and septicemia, 5 pulmonary thromboembolism, 6 pyelonephritis, 7 and cancer in general. 8 Some patients in these papers are administratively still “children,” 1 , 3 , 7 some are adults, and appendicitis is discussed in both.…”
Section: To the Editormentioning
confidence: 99%
“…Several recent papers discuss delays of diagnosis and treatment of non-COVID-19 diseases during the pandemic, including head and neck cancer, 2 appendicitis, 3 , 4 heart failure and septicemia, 5 pulmonary thromboembolism, 6 pyelonephritis, 7 and cancer in general. 8 Some patients in these papers are administratively still “children,” 1 , 3 , 7 some are adults, and appendicitis is discussed in both. 3 , 4 The delay the COVID-19 pandemic has caused in the timely diagnosis of various diseases is not a “pediatric” challenge, but a challenge for medicine in general.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation